Estimation of Intensity Patterns and Distribution of Aridity Indices over Selected Zones of Iraq Using Different Computational Methods - Abdulwahab Mohammad Younis (Tikrit Journal of Engineering Sciences)
The purpose of the present study is to identify the prevailing climate classification in the area covered by the study using different drought indicators. The current study area included eight climate stations distributed in different regions of Iraq, including northern, central, and southern Iraq. The stations included (Basra, Sammawa, Hilla, Baghdad, Ramadi, Kirkuk, Mosul and Sinjar). Data related to the study were collected from rain and temperatures from 1980-2021. Nine types of drought indicators were used in the study, the most common and commonly used in hydrological studies related to drought classifications, despite the large variation in temperature and rainfall amounts recorded within the area covered by the study. Most indicators used in the study classified the prevailing climate in the study area as falling within the dry and moderate drought climate category, with some exceptional cases for some methods due to the progression of the climate classification table and the difference in temperatures. During the seasons of the year, the study showed that the Emberger Aridity Index (EAI) is not suitable to indicate the classification of Iraq’s climate due to the large difference in temperatures between summer and winter, while the Minar's Moisture Content (J) index indicated that the desert climate is prevalent in all study areas and is the driest category for this index. Seasonal Aridity Index (SAI), which depends on rainfall and seasonal temperatures,  classified the study area within the dry, moderate dry, and semi-humid climates. The Lange and the UNEP indices classified 62.5% of the study area as an arid region and 25% as semi-arid, while the remaining part was classified as dry semi-humid. The study showed that the dry climate was the reason for the scarcity of water resources available to implement the agricultural and food security plan.